2021
DOI: 10.2174/1874471014999210112205535
|View full text |Cite
|
Sign up to set email alerts
|

Accelerator Production of Scandium Radioisotopes: Sc-43, Sc-44, and Sc-47

Abstract: Scandium radioisotopes are increasingly considered viable radiolabels for targeted molecular imaging (Sc-43, Sc-44) and therapy (Sc-47). Significant technological advances have increased the quantity and quality of available radioscandium in the past decade, motivated in part by the chemical similarity of scandium to therapeutic radionuclides like Lu-177. The production and radiochemical isolation techniques applied to scandium radioisotopes are reviewed, focusing on charged particle and electron linac initiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 0 publications
1
15
0
Order By: Relevance
“…It is also possible to produce 47 Sc through proton bombardment of titanium targets [ nat Ti(p,x) 43 , 44g , 47 Sc,48 Ti(p,2n) 47 Sc,50 Ti(p,α) 47 Sc]. These reactions suffer from co-production of 46 Sc and 48 Sc at high energies (>30-35 MeV) so lower proton energies are ideal (Chernysheva, et al, 2021). There are also two reaction routes to 47 Sc from calcium target material: 48 Ca(p,2n) 47 Sc and 44 Ca(α,p) 47 Sc (Minegishi, et al, 2016;Sitarz, et al, 2018;Wibowo et al, 2021;Aikawa, et al, 2022).…”
Section: /44gmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also possible to produce 47 Sc through proton bombardment of titanium targets [ nat Ti(p,x) 43 , 44g , 47 Sc,48 Ti(p,2n) 47 Sc,50 Ti(p,α) 47 Sc]. These reactions suffer from co-production of 46 Sc and 48 Sc at high energies (>30-35 MeV) so lower proton energies are ideal (Chernysheva, et al, 2021). There are also two reaction routes to 47 Sc from calcium target material: 48 Ca(p,2n) 47 Sc and 44 Ca(α,p) 47 Sc (Minegishi, et al, 2016;Sitarz, et al, 2018;Wibowo et al, 2021;Aikawa, et al, 2022).…”
Section: /44gmentioning
confidence: 99%
“…Like the calcium targets, nat Ti targets are feasible for producing 43/44g Sc, but production of high radionuclidic purity 43/44g Sc requires enriched titanium ( 46 Ti and 47 Ti) targets due to reactions on other stable isotopes of titanium ( 46 Ti, 8.25%; 47 Ti, 7.44%; 48 Ti, 73.72%; 49 Ti, 5.41%; 50 Ti, 5.18%). The 46 Ti(p,α) 43 Sc and 47 Ti(p,α) 44g Sc reaction routes have lower cross sections than protoninduced 43/44g Sc reactions on calcium target material, but 46 Ti and 47 Ti are cheaper than the enriched calcium material, and may also handle higher currents (Chernysheva, et al, 2021). Domnanich et al, 2017a, reported a 90-120 μAh, 15.1 ± 1.9 MeV proton irradiation of 10 mg of 97.0% ± 0.02% isotopically enriched 46 TiO 2 targets produced 1.17-1.22 MBq/μAh 43 Sc with 98.2% ± 0.3% radionuclidic purity.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has demonstrated the therapeutic suitability of 47 Sc with the diagnostic analogue 44 Sc [1,2,3]. In practice there are almost more than 10 reactions are reported to produce 47 Sc which includes using both reactors and accelerators [4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37] and by taking Ti, V or Ca as target materials. When it comes to accelerators, cyclotrons with proton beams are available in large numbers compared to other charged particle accelerator facilities.…”
Section: Introductionmentioning
confidence: 99%
“…With the 70 MeV proton cyclotron installed at the INFN-LNL, the research activities carried out within Laboratory of Radionuclides for Medicine (LARAMED) are focused on the production of emerging radionuclides with proton beams [ 2 ]. Among the radionuclides of major interest for our team is 47 Sc, a theranostic radionuclide that presents suitable decay characteristics for SPECT imaging and β − therapy ( Table 1 ), which can be also paired with the β + emitter counterparts 43 Sc and 44 Sc for PET applications [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. The lack of 47 Sc production is limiting its use in preclinical and clinical trials; for this reason, the 47 Sc proton-based production routes have been investigated within the PASTA and REMIX projects [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%